IMPLEMENTASI JARINGAN KABEL DAN WIRELESS MENGGUNAKAN ROUTER MIKROTIK PADA SD MUHAMMADIYAH 1 JAKARTA - Amin, Ahmad Sakhowi; Harsanto, Kukuh; Samsinar, Riza (SKANIKA: Sistem Komputer dan Teknik Informatika, 2022)
The research was conducted at SD Muhammadiyah 1 Jakarta. The purpose of this research is to create and implement a wired and wireless based on a mikrotik router at SD Muhammadiyah 1 Jakarta. In this research, the writer uses Mikrotik RB750r2 and Winbox application. The type of research used in this research is qualitative research. This method was chosen because qualitative research is a type of descriptive research that tends to use the process of analyzing and showing meaning. Qualitative research is research with a survey model where data and statements are obtained from the results of direct interactions between researchers, research subjects, and people at the research location. The result of the research is that the manufacture of wired and wireless using a mikrotik router has been running as it should. So that it can be used by teachers, employees and all students. This certainly provides benefits in supporting learning activities in the school environment. The user authentication to access the internet network is not only protected at the access point network, hotspot also protected by the mikrotik system, so that whenever a user wants to connect, they must login according to the SSID at SD Muhammadiyah 1 Jakarta.